High EGFL7 expression may predict poor prognosis in acute myeloid leukemia patients undergoing allogeneic hematopoietic stem cell transplantation. Issue 10 (3rd October 2019) - Cheng, Zhiheng; Dai, Yifeng; Pang, Yifan; Jiao, Yang; Liu, Yan; Cui, Longzhen; Qian, Tingting; Quan, Liang; Cui, Wei; Pan, Yue; Ye, Xu; Shi, Jinlong; et al.
ABSTRACT: Epithelial growth factor-like 7 (EGFL7) is a secretory protein with a well-characterized role in angiogenesis and the oncogenesis of certain solid tumors. Overexpression of EGFL7 is associated with adverse prognosis in patients with cytogenetically normal acute myeloid leukemia (CN-AML). However, whether this association persists after allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains unclear. To further clarify the prognostic role of EGFL7, seventy-one AML patients with EGFL7 expression data who underwent allo-HSCT from The Cancer Genome Atlas database were included and divided into either EGFL7 high or EGFL7 low group based on the median EGFL7 expression level. Two groups had similar clinical and molecular characteristics except that the EGFL7 high group had less frequent NPM1 mutations ( P = .001). Kaplan-Meier survival curves showed that high EGFL7 expressers had shorter OS than the low expressers ( P = .040). Univariate analysis showed that high EGFL7 expression, MLL-PTD, RUNX1 and TP53 mutations were associated with short OS (all P < .05). Multivariate analysis indicated that high EGFL7 expression, FLT3-ITD, RUNX1 and TP53 mutations were independent risk factors for OS (all P < .05). Collectively, our study suggested that EGFL7, like the other widely-used risk stratification factors, could serve as a prognostic tool and therapeutic target in AML, even after allo-HCST.